IMPLEMENTING THE CONSTRUCTIVIST APPROACH OF THE FACE TO FACE TUTORIAL PROGRAM IN THE ACADEMIC WRITING COURSE - Benny Agus Pribadi (Akademika, 2023)
This study aims to elaborate on using a prospective approach to improve the effectiveness of students learning achievement in the Academic Writing tutorial : program. Thirty participants were involved in a series of face-to-face tutorial programs. The objective of this program –Academic Writing - is to help teachers who enroll in a distance learning program to be able to write adequate academic papers. Since the writing process is considered a mental constructive activity, the tutors must design and implement the constructivist learning perspectives in this course. To attain the course objective, the participants had to involve in several learning assignments that employed constructivist learning design. Six elements of the constructivist learning design - Situation, Groupings, Bridge, Questions, Exhibit, and Reflections - were applied in this research. The pre-test and post-test research designs were implemented in this study. Besides, the portfolio assessment was also used to assess the participants’ learning outcomes in completing their assignments - writing their academic papers. The study results show that implementing the constructivist approach significantly increases the motivation and the ability of the students to write academic papers in the Academic Writing course of the Teacher Education Program of Universitas Terbuka